2021
DOI: 10.1002/bmc.5066
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study of three different formulations of l‐tetrahydropalmatine in brain tissues of rats

Abstract: l‐Tetrahydropalmatine (l‐THP), an active alkaloid compound isolated from Rhizoma Corydalis‐yanhusuo, has been reported to possess biological activity for treating cocaine use. To enhance both oral bioavailability and brain penetration, three formulations of l‐THP suspension, mixture of l‐THP–puerarin and self‐microemulsifying drug delivery systems (SMEDDS) were prepared. A sensitive and reliable ultra‐high‐performance liquid chromatography with tandem mass spectrometry method was developed and validated for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To improve absorption efficiency, the absorption level and rate of THP in a self-microemulsifying drug delivery system (SMEDDS) pellet formulation are higher than those of raw excipients( Tran et al, 2016 ). The SMEDDS improved the oral bioavailability of THP in a rabbit model by 198.63% ( Tung et al, 2018 ) and in a rat model by 225% ( Li et al, 2021 ) compared with THP suspension. The figures for self-emulsifying drug-delivery systems were 33.2% in a rat model ( Ma et al, 2012 ) and 234.77% for binary amorphous solid dispersion application in rabbit plasma ( Tung et al, 2021 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…To improve absorption efficiency, the absorption level and rate of THP in a self-microemulsifying drug delivery system (SMEDDS) pellet formulation are higher than those of raw excipients( Tran et al, 2016 ). The SMEDDS improved the oral bioavailability of THP in a rabbit model by 198.63% ( Tung et al, 2018 ) and in a rat model by 225% ( Li et al, 2021 ) compared with THP suspension. The figures for self-emulsifying drug-delivery systems were 33.2% in a rat model ( Ma et al, 2012 ) and 234.77% for binary amorphous solid dispersion application in rabbit plasma ( Tung et al, 2021 ).…”
Section: Pharmacokinetic Characteristicsmentioning
confidence: 99%
“…A small number of SEDDS-based products have already been successfully introduced into the pharmaceutical market, with none of them loading drugs for the treatment of neurological disorders. Until now, several in vivo assays using oral SEDDS have been carried out for neuropharmaceuticals brain targeting [ 4 , 6 , 23 , 24 , 25 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 70 ], but only a few in vivo pre-clinical studies have been reported for IN administration of neurotherapeutics loaded in SEDDS. In fact, only six studies were found that investigated the IN administration of neurotherapeutics loaded in SEDDS: clonazepam [ 45 ], diazepam [ 44 ], and perampanel [ 28 ] for epilepsy treatment; Bdph for glioblastoma treatment [ 4 ]; huperzine A [ 30 ] for Alzheimer’s disease; and naringin [ 5 ] as a neuroprotective for Alzheimer’s and Parkinson’s disease.…”
Section: Application Of Sedds In Brain Drug Delivery—pre-clinical Stu...mentioning
confidence: 99%